Kewenangan Dan Penyelesaian Sengketa Peradilan Tata Usaha Negara (Perbandingan Indonesia Dan Korea Selatan) - Navisa, Fitria Dewi (Universitas Brawijaya, 2023)
This article aims to examine the comparison of authority and dispute resolution of the State Administrative Courts of Indonesia and South Korea. The method used is a statutory statue and comparative approach. This study shows that the Indonesian and Korean state administrative justice systems have the same deadline for filing lawsuits, administrative and judicial efforts, and active judges; and there are also differences regarding the types of lawsuits, the existence of the State Administrative Court, who are the officials in the court, the number of judges authorized to hear and to whom the appeal is addressed.